2022
DOI: 10.3390/ma15072527
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption Study of Novel Gemini Cationic Surfactant in Carbonate Reservoir Cores—Influence of Critical Parameters

Abstract: Surfactant flooding is an enhanced oil recovery method that recovers residual and capillary trapped oil by improving pore-scale displacement efficiency. Low retention of injected chemicals is desired to ensure an economic and cost-effective recovery process. This paper examines the adsorption behavior of a novel gemini cationic surfactant on carbonate cores. The rock cores were characterized using an X-ray diffraction (XRD) spectroscope. In addition, the influence of critical parameters on the dynamic adsorpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…The surfactant concentration in the flood effluent was determined using the effective potentiometric HPLC (high-performance liquid chromatography) technique. , An Agilent 1200 series HPLC system featuring an attached evaporative light scattering detector (ELSD) was utilized. Acetonitrile (C 2 H 3 N) served as mobile phase A, while a 0.1 M ammonium formate (NH 4 COOH) with a pH of 4.3 adjusted by formic acid (CH 2 O 2 ) acted as the carrier phase B.…”
Section: Experimental Workmentioning
confidence: 99%
“…The surfactant concentration in the flood effluent was determined using the effective potentiometric HPLC (high-performance liquid chromatography) technique. , An Agilent 1200 series HPLC system featuring an attached evaporative light scattering detector (ELSD) was utilized. Acetonitrile (C 2 H 3 N) served as mobile phase A, while a 0.1 M ammonium formate (NH 4 COOH) with a pH of 4.3 adjusted by formic acid (CH 2 O 2 ) acted as the carrier phase B.…”
Section: Experimental Workmentioning
confidence: 99%
“…Surfactant retention by the core sample was also evaluated by analyzing the coreflood effluent. Several evaluation methods are available in the literature, including potentiometric high-performance liquid chromatography (HPLC), ,, Hyamine titration, and UV–visible spectroscopy, among others. In this work, an Agilent 1200 series HPLC was used with acetonitrile (C 2 H 3 N) as the mobile phase A.…”
Section: Experimental Workmentioning
confidence: 99%
“…Dynamic adsorption of a cationic Gemini surfactant on Indiana limestone was studied recently. 29 Outcomes showed that decreasing the surfactant concentration and increasing the flow rates will result in decreasing surfactant retention. Most recent research shows the adsorption mechanisms of a cationic Gemini surfactant onto sandstone and carbonate rocks.…”
Section: Introductionmentioning
confidence: 99%
“…Results showed that shorter spacer length showed a smaller adsorption plateau because of the same reason. Dynamic adsorption of a cationic Gemini surfactant on Indiana limestone was studied recently . Outcomes showed that decreasing the surfactant concentration and increasing the flow rates will result in decreasing surfactant retention.…”
Section: Introductionmentioning
confidence: 99%